UJI DAYA ADSORPSI ARANG AKTIF DARI TUMBUHAN MANGROVE Avicennia marina - Rina Andayani; Mahmiah (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2021)
Indonesia has the largest mangrove forest in the world. In addition, Indonesia is also a country with the largest number of mangrove species in the world. This creates a huge potential in the utilization of mangroves in many areas of life, one of them is in the health field. Where, the majority of the plants widely used in the health sector are land plants. Charcoal has been used in the field of health for thousands years. Charcoal generally utilized in the field of health in the form of activated charcoal. Activated charcoal or activated carbon is charcoal that has been through an activation process, chemical or physical. Activated charcoal can be made from any substance containing carbon. Given that wood is a renewable raw material, the use of wood as a material manufacture of activated charcoal is recommended. In this study, the material to be used in the manufacture of activated charcoal was wood from the mangrove plant Avicennia marina. The activation process used in this study was chemical activation using ZnCl2. This study included three stages: (1) carbonization; (2) activation of charcoal; (3) adsorption test of activated charcoal. The results showed that the higher the ratio of ZnCl2 mass / charcoal mass used in the activation process, the higher the adsorption capacity of activated charcoal produced. The highest % removal of CH3COOH was obtained at a ratio of ZnCl2 mass/charcoal mass of 2 which was 30.73%.